ChemInform Abstract: Crystal Structure of Alluaudite‐Type NaMg3(HPO4)2(PO4). Issue 37 (September 2015) - Ould Saleck, Ahmed; Assani, Abderrazzak; Saadi, Mohamed; Mercier, Cyrille; Follet, Claudine; El Ammari, Lahcen
Abstract The title compound is obtained under hydrothermal conditions from a mixture of Na4P2O7, MgO, and H3PO4 (85 wt%) in the molar ratio of 1:3:3 (autoclave, 483 K, 4 d).